Biodegradable Antimicrobial Polycarbonates with In Vivo Efficacy against Multidrug‐Resistant MRSA Systemic Infection. Issue 14 (1st September 2015) - Cheng, Junchi; Chin, Willy; Dong, Huihui; Xu, Liang; Zhong, Guansheng; Huang, Yuan; Li, Lanjuan; Xu, Kaijin; Wu, Min; Hedrick, James L.; Yang, Yi Yan; Fan, Weimin
Abstract : The threat of multidrug resistance requires development of new medicines to treat methicillin‐resistant Staphylococcus aureus (MRSA) infection. The biodegradable polycarbonates that have broad‐spectrum antibacterial activity and show the highest selectivity toward S. aureus are studied for their antibacterial properties against clinically isolated MRSA and toxicity both in vitro and in vivo. Minimum inhibitory concentrations of the polymers are demonstrated to be much lower than those of cefoxitin (a commonly used antibiotic) against all 31 isolates but slightly higher than those of vancomycin, a last resort medication for treating severe Gram‐positive drug‐resistant bacterial infections. Both polymers show low hemolytic activity toward human red blood cells, making them highly selective toward MRSA in vitro. A time‐kill study reveals that these polymers have high bactericidal efficiency and eradicate MRSA more rapidly than vancomycin. Results from a resistance development study also attests to the polymers low tendency toward resistance. Furthermore, the in vivo study shows that one of the polymers is highly efficacious in a mouse systemic infection model, and reduced MRSA counts in the blood more promptly than vancomycin. The administration of the polymer to mice further indicates that it did not cause any dysfunctions of liver and kidney as well as blood electrolytes. This is the first example of a polymeric therapeutics for treating systemic MRSA infection. Taken together, the biodegradable antimicrobial polycarbonate may be a better candidate for treating MRSA infection. Abstract : The antimicrobial polycarbonate with the optimized compositions is highly efficacious in treating methicillin‐resistant Staphylococcus aureus (MRSA) systemic infection without causing any dysfunctions of liver and kidney as well as blood electrolytes. It reduces MRSA counts in the blood more promptly than vancomycin and has low tendency toward resistance.